La place du fonctionnement affectif dans l’expérience muséale - Emeline Trion (Les Cahiers de l'École du Louvre)
In the late 19th century, museographic devices diversified in order to appeal to the emotions. Many of today’s exhibition designs have the same intention: offering the public a strong and memorable experience. Could appealing to the emotions of visitors be the way to provide them with an optimal museum experience? Despite the widespread use of audience research in the 1990s, few studies are able to answer this question. This article presents a master’s thesis from the École du Louvre, part of a programme launched at the Université de Montreal in 1997 under the supervision of Colette Dufresne-Tassé, which aimed to systematically study the psychological functioning of adult visitors through their discourses collected during the visit. It develops a pre-existing research instrument in an attempt to grasp the nature, place and role of affective phenomena during the museum experience.